Half a life - Naipaul, V. S. (Vidiadhar Surajprasad), 1932- (New York : Picador, 2001)
"Half a Life is the story of Willie Chandran, whose father, heeding the call of Mahatma Gandhi, turned his back on his brahmin heritage and married a woman of low caste - a disastrous union he would live to regret, as he would the children that issued from it. When Willie reaches manhood, his flight from the travails of his mixed birth takes him from India to London, where, in the shabby haunts of immigrants and literary bohemians of the 1950s, he contrives a new identity.
This is what happens as he tries to defeat self-doubt in sexual adventures and in the struggle to become a writer - strivings that bring him to the brink of exhaustion, from which he is rescued, to his amazement, only by the love of a good woman. And this is what happens when he returns with her - carried along, really - to her home in Africa, to live, until the last doomed days of colonialism, yet another life not his own."--BOOK JACKET.
DELL
Keywords: East Indians -- England -- Fiction; Colonies -- Fiction; Authors -- Fiction; Portugal -- Colonies -- Africa -- Fiction; London (England) -- Fiction; Africa -- Fiction; Psychological fiction